2020
DOI: 10.5530/pj.2020.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pteridophyta in Lubuak Mato Kuciang Padang Panjang, Sumatera Barat

Abstract: Padang Panjang city located at an altitude of 650 to 850 meters above sea level, so that weather cold and cool. Temperatures range from 17 °C to 26.1 °C and with 3,295 mm/ year of rainfall. This area is rich in the diversity of flora and fauna. Pteridophyta is one of the flora that has a unique diversity of species and has the potential for tremendous utilization such as ornamental plants, medicines and vegetable plants. The study was conducted in the Lubuak Mato Kuciang area of Padang Panjang City, West Sumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…subpectinata was identified as fern species indicating moderate disturbance. A study on the diversity of ferns in Lubuak Mato Kuciang as an area developed for tourism in West Sumatra showed the presence of two species belonging to the Gleicheniaceae, namely Dicranopteris linearis and Gleichenia linearis (Diliarosta et al 2020). Studies on the diversity of ferns in another region in Southeast Asia were also reported by a number of researchers, some of which also revealed the presence of species belonging to the Gleicheniaceae.…”
Section: Introductionmentioning
confidence: 92%
“…subpectinata was identified as fern species indicating moderate disturbance. A study on the diversity of ferns in Lubuak Mato Kuciang as an area developed for tourism in West Sumatra showed the presence of two species belonging to the Gleicheniaceae, namely Dicranopteris linearis and Gleichenia linearis (Diliarosta et al 2020). Studies on the diversity of ferns in another region in Southeast Asia were also reported by a number of researchers, some of which also revealed the presence of species belonging to the Gleicheniaceae.…”
Section: Introductionmentioning
confidence: 92%
“…(Amalia, 2009) menemukan 29 jenis tumbuhan paku dengan famili terbanyak adalah Dennstaedtiaceae di Kawasan Hutan Antibar Mempawah Timur. (Purnawati, Turnip, & Lovadi, 2014) (Sugiarti, 2017) menemukan 15 jenis tumbuhan paku dengan famili terbanyak Dennstaedtiaceae di Kawasan Cagar Alam Pagerwuyung (Diliarosta, Ramadhani, & Indriani, 2020) menemukan 21 jenis tumbuhan paku di Kawasan Lubuak Mato Kuciang Padang Panjang. Pemanfaatan tummbuhan paku di Kawasan CA Mandor dan CA Darupono masih sebatas tanaman konservasi dan sebagai tanaman hias.…”
unclassified